Exploring customer satisfaction with self-service kiosk in fast food: a study among UiTM Permatang Pauh students / Nur Najihah binti Ramli ... [et al.] - Ramli, Nur Najihah; Badrulhisham, Nurul Syamizza; Bibit, Nur Syahira; Ismail, Anida; Mohamed Apandi, Siti Rohimi (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
Self-service kiosks enable businesses to operate more quickly and cost-effectively while increasing productivity. Visitors can perform self-service tasks without waiting for professional assistance, allowing employees to work on tasks of excellent value to customers or benefit from face-to-face meetings. This study aims to measure customer satisfaction levels using self-service kiosks of fast-food restaurants. This study used a quantitative methodology and stratified random sampling technique. The sample size consisted of UiTM Cawangan Permatang Pauh students who had used self-service kiosks at fast food restaurants. The sample size was calculated using Raosoft.com, and the estimation was that the appropriate sample size for this population was 360 respondents. This research reveals a relationship between ease of use, speed of delivery, and perceived risk towards customer satisfaction among the young generation. This research also provides readers with extended knowledge about customer satisfaction that they can apply to their decision-making regarding repeating self-service kiosks at fastfood establishments. The result of this study will help fast-food restaurants identify possible surveys to utilize their services to become more popular and seek to meet client demand to optimize their revenue.